Geomagnetic Survey In Cangar Area, Batu City, East Java To Assess the Potential of Geothermal - Akhmad Afandi; Sukir Maryanto; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2012)
The prospect ofgeothermal field of Cangar’s in Batu, East Java has been observed based on the geomagneticmethod using aProtonPrecisionMagnetometer (PPM-856).The purpose is to know the magnetic anomalies around the geothermal area. The resultsshown that the residual anomaly distributed in the range of -1.000 nT to 680 nT and the low anomaly(negative) at about -1.000nTlocatedonthe northand westof themanifestations ofhotwater. Geothermalpotential based on the subsurfacemodeling of the structures on the line A-B at position 49 M 0669,071.13174 mT UTM 9,144,184.60107 mU has a value of susceptibilitycontrast of -3.166with a volume of ± 1,550,345m3. Furthermore, on the line C-D at position 49 M 0669,168.601085 mT UTM 9,143,915.10292 mU shown a value of susceptibilitycontrast at -0.018with thevolume of ± 16,610m3.